Altered tongue muscle contractile properties coincide with altered swallow function in the adult Ts65Dn mouse model of down syndrome - Glass, Tiffany J.; Russell, John A.; Fisher, Erin H.; Ostadi, Marziyeh; Aori, Nanyumuzi; Yu, Y. Eugene; Connor, Nadine P. (Frontiers in Neurology, 2024)
Purpose Down syndrome (DS) is a developmental disability associated with difficulties in deglutition. The adult Ts65Dn mouse model of DS has been previously shown to have differences in measures of swallowing compared with euploid controls. However, the putative mechanisms of these differences in swallowing function are unclear. This study tested the hypothesis that the Ts65Dn genotype is associated with atypical measures of tongue muscle contractile properties, coinciding with atypical swallow function. Methods Adult (5-month-old) Ts65Dn (n = 15 female, 14 male) and euploid sibling controls (n = 16 female, 14 male) were evaluated through videofluoroscopy swallow studies (VFSS) to quantify measures of swallowing performance including swallow rate and inter-swallow interval (ISI). After VFSS, retrusive tongue muscle contractile properties, including measures of muscle fatigue, were determined using bilateral hypoglossal nerve stimulation. Results The Ts65Dn group had significantly slower swallow rates, significantly greater ISI times, significantly slower rates of tongue force development, and significantly greater levels of tongue muscle fatigue, with lower retrusive tongue forces than controls in fatigue conditions. Conclusion Tongue muscle contractile properties are altered in adult Ts65Dn and coincide with altered swallow function.